2015
DOI: 10.3390/ijerph120505284
|View full text |Cite
|
Sign up to set email alerts
|

The Negative Affect Hypothesis of Noise Sensitivity

Abstract: Some studies indicate that noise sensitivity is explained by negative affect, a dispositional tendency to negatively evaluate situations and the self. Individuals high in such traits may report a greater sensitivity to other sensory stimuli, such as smell, bright light and pain. However, research investigating the relationship between noise sensitivity and sensitivity to stimuli associated with other sensory modalities has not always supported the notion of a common underlying trait, such as negative affect, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 46 publications
0
25
2
Order By: Relevance
“…A recent epidemiological study reports that up to 88% of individuals with high noise sensitivity self-declare at least one other environmental sensitivity17. However, research does not always confirm the relation between NS and negative evaluations in other sensory dimensions4950. According to the findings of this study, NS is selectively associated with alteration of neuronal processing of noise, but not of intensity, location, frequency or rhythm contour changes.…”
Section: Discussioncontrasting
confidence: 74%
“…A recent epidemiological study reports that up to 88% of individuals with high noise sensitivity self-declare at least one other environmental sensitivity17. However, research does not always confirm the relation between NS and negative evaluations in other sensory dimensions4950. According to the findings of this study, NS is selectively associated with alteration of neuronal processing of noise, but not of intensity, location, frequency or rhythm contour changes.…”
Section: Discussioncontrasting
confidence: 74%
“…There may have been self-selection out of the noisiest areas or not into noisy areas, even at baseline, for the most noise sensitive, or this could have occurred during follow up. However, mobility of noise sensitive persons out of noisy areas has not been found in other studies [35].…”
Section: Discussionmentioning
confidence: 63%
“…Neuroticism is a construct similar to trait anxiety and has links to negative affectivity, a tendency to report life experiences and perceptions negatively. Noise sensitivity does not seem to be just trait anxiety or neuroticism and Shepherd et al [35] have found higher correlations with introversion/extraversion than with neuroticism [43]. A question often asked in this literature is how speci c is noise sensitivity to noise or much is it part of a wider range of responses to environmental stimuli driven largely by chronic anxiety [44]?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between negative affectivity and noise sensitivity still remains controversial [114]. …”
Section: Discussionmentioning
confidence: 99%